Objects from prehistory, a study from the point of view of ergonomics – a reference in Brazil - Menin, Mariana [UNESP] (Taylor & Francis, 2012)
The Ergonomics has the exact date of its birth but the events preceding the formal launching of today are little explored. Specifically this issue in Brazil is still little explored in books or conference proceedings that area. The article aims to reflect and discuss the development of ergonomics in the prehistory, specifically in Brazil through sample of lithic artifacts from museums of the cities in the State of Sao Paulo. Thus, archaeological remains of instrument from chipped stone are important to research the history that precedes the formal launching of Ergonomics in Brazil and the world and to understand the criteria that the man was sought, unconsciously, comfort, safety and ease in building their tools.
Keywords: Ergonomics; Prehistory; Tools